Feasibility of Routinely Offering Early Combined Antiretroviral Therapy to HIV-infected Infants in a Resource-limited Country: The ANRS-PediaCAM Study in Cameroon. Issue 10 (October 2015) - Tejiokem, Mathurin Cyrille; Warszawski, Josiane; Ateba Ndongo, Francis; Tetang Ndiang, Suzie; Ndongo, Jean Audrey; Owona, Félicité; Ngoupo, Paul Alain; Tchendjou, Patrice; Kfutwah, Anfumbom; Penda, Ida Calixte; Faye, Albert
Abstract : Background: Early diagnosis of HIV is increasingly available for infants in resource-limited settings. We assessed the timing of events until combined antiretroviral therapy (cART) initiation in infants diagnosed before 7 months of age in Cameroon. Methods: The ANRS-PediaCAM cohort included HIV-infected infants followed from birth associated with prevention of mother-to-child transmission activities (group 1) or diagnosed for any other reason before 7 months of age (group 2). All infants were offered free cART early after diagnosis. Frequency and factors associated with no or delayed cART initiation, were studied using univariable and multivariable logistic regressions. Results: Between 2007 and 2011, 210 HIV-infected infants (group 1: 69; group 2: 141) were included. Fewer group 1 (14.3%) than group 2 (59.1%) infants were symptomatic (World Health Organization stage 3 or 4). Overall, 5.7% (n = 12) died before receiving any cART. Of the remaining 198 infants, 3.0% (n = 6) were not treated. The median age at initiating cART was 4.1 months [interquartile range (IQR): 3.2–5.6]. The median time until cART initiation after HIV testing was 6.2 weeks (IQR: 4.4–9.4) in group 1 and 5.1 weeks (IQR: 2.9–9.4) in group 2. No or delayed cART, observed for 37.9% (75 of 198) of the infants, was associated with clinical site [adjusted odds ratio (aOR): 4.8; 95% confidence interval: (2.1–11.2)], late diagnosis [aOR: 2.0 (0.9–4.1)], and delayed pretherapeutic biological assessment [aOR: 3.7 (1.4–10.0)]. Conclusions: Although most children included were treated before age 7 months, the initiation of therapy was delayed for more than 1 in 3. The period around HIV diagnosis is critical and should be better managed to reduce delays before cART initiation.